Reliability and validity of the Chinese version of Supervision Evaluation and Supervisory Competence Scale - Zou Hongrong; Xu Jun; Wang Jing; Zhang Ya (Sichuan jingshen weisheng)
BackgroundClinical supervision is a critical component in the training and professional development of psychological counselors. Scientifically evaluating the effectiveness of clinical supervision is essential， yet reliable and effective tools for such assessments are lacing in China.ObjectiveTo translate Supervision Evaluation and Supervision Competence （SE-SC） Scale into Chinese version and evaluate its reliability and validity in clinical supervision in China， so as to provide a tool for the evaluation of supervisory effectiveness.MethodsThe SE-SC scale was translated， back-translated and culturally adapted， followed by a pilot survey to develop the Chinese version of SE-SC scale. A total of 42 counselors engaged in clinical counseling and receiving supervision at a counseling center in Shanghai from July 2021 to February 2022 were selected as the study participants. Item analysis was conducted to assess item discrimination， with critical ratio method applied to determine which items retention. Hierarchical cluster analysis was performed to compare the structure of Chinese version with the original scale. Criterion-related validity and convergent validity were used to evaluate the validity of the scale， while Cronbach's α coefficient was used to assess its reliability.ResultsChinese version of SE-SC scale consisted of a total of 28 item， including six clusters. Registered supervisors scored significantly higher than internship supervisors on the total score and on clusters three， four， five and six （t=2.536， 2.747， 5.881， 3.718， 6.090， P<0.05）. The total and cluster scores of the Chinese version of the SE-SC scale were positively correlated with self-rated supervision helpfulness and overall satisfaction （r=0.492~0.758， 0.412~0.815， P<0.01）. The Cronbach's α coefficient for the overall scale was 0.975，with values for the six clusters were 0.938， 0.821， 0.962， 0.871， 0.884 and 0.823， respectively.ConclusionChinese version of SE-SC scale demonstrates good reliability and validity， and it can be considered as a promising assessment tool for evaluating the effectiveness of clinical supervision.